PENGARUH PELATIHAN, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP PRESTASI KERJA PEGAWAI DINAS KEARSIPAN DAN PERPUSTAKAAN KABUPATEN PASAMAN - Ria Widhia Sari; Wendra Wendra (Jurnal Menara Ekonomi : Penelitian dan Kajian Ilmiah Bidang Ekonomi, 2020)
Abstract: This study aims to examine the effect of training, motivation and work environment on employee performance in the Archives and Pasaman District Library. The first hypothesis tested the effect of training on employee performance in the Archives and Pasaman District Library Office. The second hypothesis examines the effect of motivation on the achievements of the Pasaman District Archives and Library employees. The third hypothesis examines the influence of the work environment on employee performance in the Archives and Library of Pasaman Regency. The fourth hypothesis examines the effect of training, motivation and work environment on employee achievement of the Office of Archives and Library of Pasaman Regency together. The population in this study were employees of the Archives and Pasaman District Library Office. Samples This study uses a saturated sampling technique. Research data were collected by the method and analyzed by multiple linear regression. The results of the first hypothesis research show that a significant value of 0.154> alpha 0.05 so that training does not have an influence on employee performance in the Archives and Library of Pasaman Regency. The results of the second hypothesis show that a significant value of 0.002